Towards sustainable shrimp culture in thailand and the region : (Australian Centre for International Agricultural Research Canberra, 1999)
Shrimp farming expanded rapidly in Thailand and other countries in Asia in the early 1990s, but productivity plateaued and then went into decline. This text contains the findings of an ACIAR-funded project titled "Key researchable issues in sustainable coastal shrimp aquaculture in Thailand".